Resiliensi Civil Society Di Tengah Polarisasi Sosial-Politik Dalam Perspektif Demokrasi Deliberatif - Erfain Erfain (FKIP UNSULTRA, 2025)
The increasingly sharp socio-political polarization in recent years has posed serious challenges to the sustainability of democracy in various countries, including Indonesia. This polarization not only divides society, but also erodes public trust in democratic institutions. In the midst of these conditions, the existence and role of civil society become crucial as a balancing force that is able to mediate differences and strengthen the democratic order. This study aims to analyze how civil society resilience is formed and functions in the context of socio-political polarization through the perspective of deliberative democracy. With a literature study approach, this article examines a number of previous studies that discuss the dynamics of civil society, the concept of social resilience, and the practice of democratic deliberation. The results of the study show that civil society that has high resilience tends to be supported by reflective capacity, cross-identity collaborative networks, and the ability to build inclusive deliberative spaces. This resilience allows civil society organizations to continue to play an active role in voicing public interests, encouraging policy transparency, and building solidarity amidst social fragmentation. Thus, deliberative democracy becomes a relevant framework for understanding and strengthening the function of civil society in overcoming socio-political polarization. This study concludes that strengthening deliberative capacity in civil society is key to maintaining social cohesion and strengthening participatory democracy.